Global-mindedness Through the Eyes of EFL Learners: Gender and Level of Proficiency in Focus - Fatalaki, Javad Ahmadi; Zhang, Runhan (Lesya Ukrainka Eastern European National University, 2016)
The major aim of the present study is to find connections between global-mindedness and some important factors such as gender and level of proficiency. To this end, 182 language learners, 92 females and 90 males, participated in the study. These students were selected and categorized based on one-stage cluster sampling from 16 branches of different language centers, namely Safiran, Shoukoh, and Kish. The main phase of the study was conducted through the use of Google Docs platform that provides the researchers with the well-organized data. Language learners were asked to answer all the demographic information by considering their anonymity during the process of data collection. The result of the study, through t-test, showed that there was a significant difference between male and female language learners regarding their level of global-mindedness. The result also showed that the level of proficiency of the female language learners does not influence their level of global-mindedness.Мета дослідження полягає в знаходженні зв'язку між глобальним мисленням і деякими важливими чинниками, як-от стать і рівень майстерності. У дослідженні взяло участь 182 особи, з яких 92 особи жіночої статі та 90 осіб чоловічої статі. Студенти були відібрані і поділені на групи за принципом одноступінчастого кластеру з вибіркою 16-ти філіалів різних мовних центрів, а саме «Сафіран», «Шоуко», і «Кіш». Основний етап дослідження було проведено за допомогою використання сервісу Google Docs, що забезпечує дослідників добре впорядкованими даними. Студентам було запропоновано надати повну демографічну інформацію про себе зі збереженням принципу анонімності протягом процесу збору даних. Результати Т-тесту (t-критерій Стьюдента) показали велику різницю глобального мислення між мовою осіб чоловічої і жіночої статі. Серед студентів жіночої статі вагомої різниці між глобальним мисленням і рівнем володіння мовою не було виявлено.
Keywords: global-mindedness; gender; EFL; communication; level of proficiency; глобальне мислення; гендер; англійська мова як іноземна; комунікація; рівень володіння мовою